A Generalization of the Doubling Construction for Sums of Squares Identities - Zhang, C.; Huang, H.L. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
The doubling construction is a fast and important way to generate new solutions to the Hurwitz problem on sums of squares identities from any known ones. In this short note, we generalize the doubling construction and obtain from any given admissible triple [r,s,m] a series of new ones [r+ρ(2ⁿ⁻¹),2ⁿs,2ⁿm] for all positive integer n, where ρ is the Hurwitz-Radon function.